A salivary elicitor MsPDI3 from Mythimna separata triggers plant defense responses - Jin-Da Wang; Huan-Tai Lin; Lin Li; Yao-Hui Chen; Ran Wang; Honglin Feng; San-Ji Gao (Insect Biochemistry and Molecular Biology, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Comprehensive investigations reveal high occurrence of tet(X) in blaNDM-positive Acinetobacter spp. from Chinese cattle production systems - Weiwei Wang; Qing Wang; Yanhua Qiu; Guonian Dai; Bing Li; Honglin Lin; Yaxin Zhou; Jiyu Zhang (International Journal of Food Microbiology, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Cell size as a biomarker for proliferation in Noctiluca scintillans: Insights from controlled experiments - Nanjing Ji; Qiuping Li; Xiaotong Cheng; Yifan Chen; Honglin Chen; Yinghao Wang; Bin Han; Gewei Chen; Xin Shen; Senjie Lin (Marine Pollution Bulletin, 2026)

An R2R3-MYB transcription factor TgMYB44 positively regulates petal senescence by enhancing ABA biosynthesis in tulip - Haipo Yang; Yikun Wu; Chengxiao Yuan; Hongqing Yin; Lin Xiang; Xuewei Wu; Honglin Deng; Bo Sun; Zhulong Chan; Yanping Wang (Plant Cell Reports, 2026)

Predicting the performance of microbial electrochemical systems equipped with three-dimensional anodes using machine learning - Jiannan Li; Honglin Chen; Yijie Lin; Hongbo Mai; Yanfang Song; Ye Qiu; Guohong Liu; Yujie Feng (Journal of Environmental Chemical Engineering, 2025)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Development of a sensitive simultaneous analytical method for 26 targeted mycotoxins in coix seed and Monte Carlo simulation-based exposure risk assessment for local population - Chuiwei Liu; Weisheng Xu; Lei Ni; Huafeng Chen; Xiangju Hu; Honglin Lin (Food Chemistry, 2024)

Multi-omics analysis of attenuated variant reveals potential evaluation marker of host damaging for SARS-CoV-2 variants - Guangshan Xie; Lin Zhu; Siwen Liu; Cun Li; Xin Diao; Yanhao Zhang; Xiuli Su; Yuanyuan Song; Guodong Cao; Li Zhong; Pui Wang; Xiaojuan Liu; et al. (Science China Life Sciences, 2024)

Molecular cloning, expression, and functional analysis of a putative lectin from the pearl oyster (Pinctada fucata, Gould 1850) - Peng Liu; Wenyue Li; Yue Peng; Siyin Han; Zhongxiu Liang; Yanhui Cen; Xinrong Li; Peiyan Wang; Huiying Lv; Qingying Zhang; Honglin Chen; Jiang Lin (Fish & Shellfish Immunology, 2023)

Proteomics reveals the underlying mechanism by which the first uneven division affects embryonic development in pig - Fuquan Zhu; Xinyue Lu; Yuan Jiang; Dayu Wang; Linqing Pan; Chao Jia; Lin Zhang; Yan Xie; Mingyue Zhao; Huijun Liu; Meixia Wang; Tingzhang Wang; et al. (Theriogenology, 2023)

Occurrence and carcinogenic risk assessment of N-nitrosamines in some dried aquatic products in China - Siting Huang; Wusheng Fu; Qinmei Fang; Lei Ni; Renjin Zheng; Ling Yong; Zheng Huang; Jie Pang; Zhong Lin; Honglin Lin; Rongde Dai (Food Control, 2023)

Cobalt nanoparticles induce mitochondrial damage and β-amyloid toxicity via the generation of reactive oxygen species - Jingrong Chen; Cheng Chen; Na Wang; Chunyu Wang; Zhaohui Gong; Jingxian Du; Honglin Lai; Xinpei Lin; Wei Wang; Xiangyu Chang; Michael Aschner; Zhenkun Guo; et al. (NeuroToxicology, 2023)

Distribution Characteristics of Soil Organic Phosphorus Fractions in the Inner Mongolia Steppe - Xiaoya Zhu; Xiaorong Zhao; Qimei Lin; Alamus; Hai Wang; Honglin Liu; Wenxue Wei; Xuecheng Sun; Yongtao Li; Guitong Li (Journal of Soil Science and Plant Nutrition, 2020)

Benzophenanthridine alkaloids suppress lung adenocarcinoma by blocking TMEM16A Ca2+-activated Cl− channels - Gaohua Zhang; Lin Zhu; Yucong Xue; Zhijun Zhao; Honglin Li; Zhiyun Niu; Xiangchong Wang; Pingping Chen; Jianping Zhang; Xuan Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Quantifying the carbon source of pedogenic calcite veins in weathered limestone: implications for the terrestrial carbon cycle - Lin Zou; Lin Dong; Meng Ning; Kangjun Huang; Yongbo Peng; Shujian Qin; Honglin Yuan; Bing Shen (Acta Geochimica, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Therapeutic Intervention of Learning and Memory Decays by Salidroside Stimulation of Neurogenesis in Aging - Huijuan Jin; Lei Pei; Xiaogang Shu; Xin Yang; Tianhua Yan; Yan Wu; Na Wei; Honglin Yan; Shan Wang; Chengye Yao; Dan Liu; Qing Tian; et al. (Molecular Neurobiology, 2016)

Identification of a novel compound heterozygous mutation in PTPRQ in a DFNB84 family with prelingual sensorineural hearing impairment - Qing Sang; Honglin Mei; Ahan Kuermanhan; Ruizhi Feng; Luo Guo; Ronggui Qu; Yao Xu; Huawei Li; Li Jin; Lin He; Lei Wang (Molecular Genetics and Genomics, 2015)

Expression profiles of key candidate genes involved in steroidogenesis during follicular atresia in the pig ovary - Zengxiang Pan; Jinbi Zhang; Fei Lin; Xueshan Ma; Xuguang Wang; Honglin Liu (Molecular Biology Reports, 2012)